REFORMASI ROYALTI MUSIK ERA DIGITAL: TRANSFORMASI NO. 56 TAHUN 2021 MENUJU SISTEM ADIL BERBASIS BLOCKCHAIN, KEADILAN ADAPTIF, DAN KEARIFAN LOKAL - Indra Jaya; Rompas, Jopie Tommy; Ananda, Selvira Paulina; Hutauruk, Appe; Maulana, Taufik; Simanungkalit, Robert L; Maharani, Shinta (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
The implementation of Government Regulation No. 56 of 2021 (PP 56/2021) concerning the Management of Song and/or Music Copyright Royalties, which was introduced as a government effort to modernize economic rights protection in the digital era through the National Collective Management Institute (LMKN), has sparked significant controversy, particularly for micro, small, and medium enterprises (UMKM) and non-commercial public services. Through a normative legal approach, the analysis shows that this regulation goes beyond the delegation of Law No. 28 of 2014 concerning Copyright by expanding the objects of collection, blurring the boundaries between commercial and non-commercial use, and creating legal uncertainty and sociological injustice. In response, this study not only critiques but also offers a reformulation of the music royalty system within the framework of PP 56/2021. This study proposes a reformulation of the royalty system through three main pillars: (1) the application of the concept of "fair use" to create adaptive justice for UMKM; (2) modernization of the system using blockchain technology and AI for transparency and distribution efficiency; and (3) integration of mechanisms for protecting regional music as a cultural heritage. The vision of this reformulation is to create a fair, transparent, and sustainable royalty ecosystem that balances the economic rights of creators, the growth of UMKM, technological innovation, and cultural preservation.